Analysis of Opportunities and Barriers in the Use of Digital Systems to Optimize Hotel Business Operations: Analisis Peluang Dan Hambatan Penggunaan Sistem Digital Dalam Mengoptimalkan Operasional Bisnis Hotel - Harji, Laisya putri; Suharto, Bambang (Jurnal Ilmiah Hospitality Management, 2024)
The hospitality industry has undergone significant changes with advancements in technology, as modern hotels increasingly rely on digital systems to improve operational efficiency and strengthen customer relationships. This study aims to conduct a comprehensive analysis of the opportunities and barriers associated with the use of digital systems in optimizing hotel business operations. In this research, we analyze various aspects influencing the implementation of digital technology in the hospitality sector, including external factors such as industry trends and regulations, as well as internal factors such as organizational culture and technological capabilities. However, alongside these opportunities, we also identify various barriers that may hinder the adoption and implementation of digital systems, including data security issues, high implementation costs, and challenges in changing organizational culture. The findings of this study are highly relevant to the hospitality industry, which continues to strive to remain competitive in this digital era. Furthermore, this research can also contribute to the academic literature on information technology management and business strategies in the hospitality sector.